Men and Death in the West. Towards a New Interpretive Paradigm? - Andrea Salvatore Antonio Barbieri (Culture e Studi del Sociale)
Up until recently, contemporary Western society seemed to voluntarily ignore death, wrapping itself in a silent cocoon. Death disappeared from the public discourse unless it was spectacularised and mediatised. While ‘true’ death receded from individual lives, ‘fake’ death was omnipresent – widespread and thus anesthetising. After being one of the great taboos of our time, it is now becoming visible again. Three aspects, which can be framed as individual civil rights, have promoted this change: bioethics (which forced the public to ponder challenging topics), cultural pluralisation (which introduced novel ways of thinking and experiencing death) and a tendency towards the creation of institutions attentive to a new humanisation of death(e.g. pandemics give rise to pandethics, with the need to harmonize individual and community rights).We are perhaps at the beginning of a cultural turning point, though punctuated with many ambivalences and contradictions. To better understand it, we should look at its antecedents and at the history of the death-related imaginary in the West. We will consider Ariès (1975) schematization of four subsequent phases in societal attitude towards death and hypothesize the beginning of a fifth stage: death postponed but also rediscovered (even if not yet truly reconciled).